An Itaconic Acid‐Based Phosphorus‐Containing Oligomer Endowing Epoxy Resins with Good Flame Retardancy and Toughness - Zhao, Huijuan; Duan, Huajun; Zhang, Junjun; Chen, Lu; Wan, Chao; Zhang, Chenhao; Liu, Chentao; Ma, Huiru (Macromolecular materials and engineering, 2023)
With the aim to reduce the influence of flammability and brittleness of epoxy resin (EP) on its applications, a phosphorus‐containing oligomer (BID) containing phosphophenanthrene group and flexible chain segment is designed and applied to methyltetrahydrophthalic anhydride (MeTHPA) curing EP systems. Compared with EP/MeTHPA, the glass transition temperature (Tg) declines after introducing BID. But the addition of BID endows EP/MeTHPA with good flame retardancy. When the dosage is only 19.2 wt.%, the limiting oxygen index (LOI) of EP/BID/MeTHPA increases by 77% to 36% (P content: 1.5 wt.%) compared with EP and reaches the vertical combustion (UL‐94) V‐0 rating. Cone calorimetry (CC) results reveal that PHRR and THR drop by 40% and 31%. The pyrolytic process and char residue data analysis show that BID plays flame‐retardant role in gas phase and condensed phase. In addition, impact and flexural and tensile strength improve by 84%, 19% and 54% individually, proving that BID holds a potential on enhancing mechanical performance of EP/MeTHPA. Phosphorus oligomer BID is applied in the EP system of methyl tetrahydrophthalic anhydride (MeTHPA) cured epoxy resin. The addition of BID not only improves the flame retardancy of EP, but also improves the mechanical properties.